Modal Parameter Tracking in a Carbon Fiber-Reinforced Structure over Different Carbon Fiber Angles - Chan-Jung Kim (MDPI AG, 2021)
The dynamics of carbon fiber-reinforced plastic (CFRP) change according to the carbon fiber angle, and a mode order shift may occur in CFRP specimens. The variation trends in modal parameters differ in each mode; thus, an efficient mode-tracking method is needed to identify the reliable dynamic behavior of the CFRP structure. The mode-tracking method was assumed to be applicable for the same configuration of the tested specimen except for the differences in carbon fiber angle of the CFRP specimen. Simple rectangular specimens were prepared for one isotropic material, SS275, and five anisotropic CFRP specimens with five carbon fiber angles ranging from 0° to 90°. An experimental impact test was conducted to obtain all the modal parameters. The proposed mode-tracking method was applied using three indicators: the modal assurance criterion (MAC) and two modal parameters (resonance frequency and modal damping ratio). The MAC value was valid for the three bending modes at 0°, 30°, and 90°, but not for the two torsional modes. However, the variation in the resonance frequencies was a more efficient indicator with which to track all the modes of interest, except for the second torsional mode. The variation in the modal damping ratio was also a valid indicator for the two torsional modes. Therefore, the proposed three indicators were all required to derive reliable mode tracking for the CFRP specimens considering the mode order shift.